2015
DOI: 10.1007/s11356-015-4325-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of ZnO nanoparticles and the released Zn(II) ion to corn (Zea mays L.) and cucumber (Cucumis sativus L.) during germination

Abstract: Toxicity of engineered nanoparticles on organisms is of concern worldwide due to their extensive use and unique properties. The impacts of ZnO nanoparticles (ZnO NPs) on seed germination and root elongation of corn (Zea mays L.) and cucumber (Cucumis sativus L.) were investigated in this study. The role of seed coats of corn in the mitigation toxicity of nanoparticles was also evaluated. ZnO NPs (1,000 mg L −1 ) reduced root length of corn and cucumber by 17 % (p<0.05) and 51 % (p<0.05), respectively, but exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(67 citation statements)
references
References 37 publications
6
61
0
Order By: Relevance
“…Our study distinctly demonstrated the dose dependent inhibition of A. cepa root length and root cell viability upon exposure to ZnO-NPs under in vitro conditions, which clearly suggests induced phytotoxicity and oxidative stress at cellular level. The results of root growth suppression assay corroborate earlier studies on the inhibition of root growth by ZnO-NPs in corn and cucumber plants41. Also, Kouhi et al 20.…”
Section: Discussionsupporting
confidence: 88%
“…Our study distinctly demonstrated the dose dependent inhibition of A. cepa root length and root cell viability upon exposure to ZnO-NPs under in vitro conditions, which clearly suggests induced phytotoxicity and oxidative stress at cellular level. The results of root growth suppression assay corroborate earlier studies on the inhibition of root growth by ZnO-NPs in corn and cucumber plants41. Also, Kouhi et al 20.…”
Section: Discussionsupporting
confidence: 88%
“…3. Similar results of declining trend of radical and plumule lengths with respect to effluent concentration was inferred by Anupama (2011), Yasmin et al (2011), Narain et al (2012a, b), and Zhang et al (2015). But in maize, ETP50 and ETP100 showed similar promoting effect on radical and plumule length.…”
Section: Seedling Lengthsupporting
confidence: 82%
“…However, our study concluded ZnO ENPs to be more The maximum amount of phytotoxicity was obtained at 2000 mg/L in the current study by which physiological parameters, SGs, and non-enzymatic antioxidant activities mitigate to a minimum. The supreme toxicity of ZnO ENPs at 1000 mg/L of concentration was elucidated in corn (Zea mays) and cucumber (Cucumis sativus) by Zhang et al [56]. Similarly, Zafar et al [14] also endorsed the toxicological phenomena at 1000 mg/L in black mustard (Brassica nigra).…”
Section: Discussionmentioning
confidence: 97%